Phonological study of the Sonaha language - Chaudhary, Anil Dutt (Contemporary Research: An Interdisciplinary Academic Journal, 2020)
The Sonaha is a language which is spoken in Bardiya, Kailali and Kanchanpur districts in Nepal. Sonaha language, henceforth Sonaha, was not identified by the government before the Census 2011. In spite of having its own linguistic features and originality, Sonaha is badly affected by the influence of other neighboring languages. Keeping this in mind, this study mainly aims to explore and present the inventory of the phoneme, syllable structures and vowel sequence or, in short, to highlight the phonological system of Sonaha language. Sonaha 3404 native words were collected from fifty native speakers of Rajapur Municipality and Geruwa Rural Municipality of Bardiya district, Ghodaghodi Municipality of Kailali and Bhimdutt Municipality of Kanchanpur district. The data were presented and analyzed based on minimal pairs to verify phonemes. This study explored six vowels, twenty nine consonants, six types of syllable structures and seven vowel sequences in Sonaha.